Study of Genetic Divergence in Advance Breeding Lines of Soybean [Glycine max (L.) Merrill] for Yield Attributing Traits - Mishra, Stuti; Jha, Avinash; Panchshwar, D. K.; Shrivastava, A. N. (International Journal of Bio-resource and Stress Management, 2018)
An investigation was conducted during Kharif 2015 with sixty advances breeding lines of soybean, to identify the most diverse and promising lines for hybridization through genetic diversity analysis by Mahalanobis’s D2 statistics. The D2 statistics is a powerful tool to measure genetic divergence within a population and to estimate the contribution of each trait to the total diversity. In present study observations on twelve yield attributing traits were recorded on lines raised with 3 replications in RBD. The results revealed significant differences among lines for all studied traits. Sixty soybean lines were grouped in 16 clusters following Tocher’s method. Cluster I was polygenotypic (14 lines) followed by cluster III (12 lines), cluster V (8 lines), cluster VIII (7 lines), XV (8 lines), while remaining 11 clusters were monogenotypic. Entries from cluster I, III, V, VIII, IX, XIII and XV can be used in hybridization programme for development of resistant and high yielding lines. The identified potential lines based on the D2 statistics were JS 20-49, JS 20-109, JS 20-116, JS 20-94, JS 21-03, JS 21-04, JS 20-79, JS 20-87, JS 20-89, JS 20-69, JS 20-98, JS 20-34, JS 20-29, JS 20-53, NRC 37, RVS 2007-1, JSM 242, JS 335, JSM 230, JS 20-86. Among twelve traits, numbers of pods plant-1, number of seeds plant-1 and seed yield plant-1 were maximum contributing traits to genetic diversity.